Calls on high‐technology: Japanese exploration of venture capital investments in the United States - Hurry, Dileep; Miller, Adam; Bowman, Edward H. (Strategic Management Journal, 1992)
Abstract The strategic logic of Japanese high‐technology venture capital investment reveals the existence of an implicit call option, or ‘shadow option’, on new technology. This option is exercised by further investment in product development, manufacturing and distribution. The process is described with reference to a comparative study of Japanese and U.S. venture capital firms. Similarities and differences between the two groups are reported, and a conceptual model of Japanese option strategy is formulated. The implications for our understanding of Japanese strategy and for strategic management theory are discussed.